The Red Vienna sourcebook - McFarland, Rob; Zechner, Ingo; Spitaler, Georg (Studies in German literature, linguistics, and culture, 2020)
An encyclopedic selection of original documents from the Austrian capital's pathbreaking, progressive interwar period, translated and with contextualizing introductions and commentaries.